Vitamin B12 and Age-Related Cognitive Decline-Dementia and "Alzheimer's Disease" - Rosenberg, Irwin H (Food and nutrition bulletin, 2024)
This article is a commentary on the role of vitamin B in age-related cognitive decline, with a meta-commentary on the misuse of the term "Alzheimer's Disease." The article describes the historical origins of the term "Alzheimer's Disease" and argues that the term should be restricted to a narrower segment of the age-related dementia spectrum. The article also outlines the role of vitamin B in age-related cognitive decline and outlines the rationale for the treatment of B deficiency to address a potentially reversible factor in cognitive decline.